1985
DOI: 10.1037/0012-1649.21.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Child care arrangements and children's functioning: A comparison of self-care and adult-care children.

Abstract: Forty-eight self-care children were compared with 48 matched children in adult care to investigate whether the self-care ("latchkey") arrangement has negative consequences for children. On several measures of children's social and psychological functioning, no significant differences were found between the two matched samples. Virtually no research has been done on self-care, even though there are large numbers of children involved. Growing public and policy concerns about self-care suggest the need for much m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 18 publications
3
41
0
1
Order By: Relevance
“…Such children were previously called ''latchkey children'' because they often wore keys to their houses around their necks (Diamond, Kataria, & Messer, 1989). In contrast to widespread belief, early research often indicated no difference between children left in self-care and children left in other arrangements where an adult was physically present Galambos & Garbarino, 1985;Messer, Wuensch, & Diamond, 1989;Rodman, Pratto, & Nelson, 1985;Steinberg, 1986;Vandell & Corasaniti, 1988). This early research, while offering a good start to the examination of the effects of self-care, has many limitations, however.…”
Section: Self-carementioning
confidence: 96%
See 1 more Smart Citation
“…Such children were previously called ''latchkey children'' because they often wore keys to their houses around their necks (Diamond, Kataria, & Messer, 1989). In contrast to widespread belief, early research often indicated no difference between children left in self-care and children left in other arrangements where an adult was physically present Galambos & Garbarino, 1985;Messer, Wuensch, & Diamond, 1989;Rodman, Pratto, & Nelson, 1985;Steinberg, 1986;Vandell & Corasaniti, 1988). This early research, while offering a good start to the examination of the effects of self-care, has many limitations, however.…”
Section: Self-carementioning
confidence: 96%
“…As college attendance can be viewed as an indicator of good academic achievement and behavioral functioning, one would hardly expect large differences on these variables with such a sample. Rodman et al (1985) were limited by their data collection method as well as their rural sample. These authors compared the self-esteem and social adjustment of children in self-care and children in maternal care and found no differences.…”
Section: Self-carementioning
confidence: 99%
“…In contrast, Galambos and Garbarino (1983) did not find a difference between fifth-and seventhgrade latchkey children and their adult-supervised counterparts with regard to achievement level, fear, and school adjustment. Rodman, Pratto, and Nelson (1985) found no significant differences between latchkey and non-latchkey children in the fourth and seventh grades on measures of self-esteem, locus of control, social adjustment, and interpersonal relationships. Vandell and Corasaniti (1988) also found no differences between latchkey and mother-care children in terms of sociometric nominations, academic grades, standardized test scores, conduct scores, and self-reports of competence.…”
mentioning
confidence: 64%
“…Most studies have found no association between self-care in elementary school-age children and behavior problems, poor social/emotional adjustment, low academic achievement, or poor school adjustment-well established correlates of deviant development; (Chueh, 1992;Denmark, 1989;Galambos & Garbarino, 1982;Lovko & Ullman, 1989;McCright, 1992;Messer, Wuensch, & Diamond, 1988;Rodman, Pratto, & Nelson, 1985;Vandell & Corasaniti, 1988).…”
Section: Self-care and Deviancementioning
confidence: 97%